2021
DOI: 10.1007/s00128-021-03252-1
|View full text |Cite
|
Sign up to set email alerts
|

Time to Safeguard the Future Generations from the Omnipresent Microplastics

Abstract: Two new cyclonerane sesquiterpenes, 5-hydroxyepicyclonerodiol oxide (1) and 4-hydroxyepicyclonerodiol oxide (2), and one new naturally occurring halogenated trichothecane derivative, trichodermol chlorohydrin (3), were isolated from Trichoderma hamatum Z36− 7, an epiphytic fungal strain obtained from the marine red alga Grateloupia sp. Their structures and relative configurations were assigned on the basis of spectroscopic techniques, including 1D/2D NMR and IR as well as MS. Compound 2 features an unusual 4-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…It is noteworthy that children are more sensitive to chemicals than adults (19). Interestingly, PSMPs are found in a variety of foods and products marketed to children, such as milk, honey, sugar, feeding bottles, and toys (20), promoting children being more vulnerable to MPs than adults. Studies have reported that PSMPs can be transferred through the placenta and generate developmental toxicity (21).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that children are more sensitive to chemicals than adults (19). Interestingly, PSMPs are found in a variety of foods and products marketed to children, such as milk, honey, sugar, feeding bottles, and toys (20), promoting children being more vulnerable to MPs than adults. Studies have reported that PSMPs can be transferred through the placenta and generate developmental toxicity (21).…”
Section: Introductionmentioning
confidence: 99%
“…Infants and toddlers are more susceptible to potential health impacts of micro- and nanoplastics than adults, making their exposure to these particles and associated health risks a significant concern. A recent study focused on the release of microplastics from polypropylene-based baby feeding bottles during formula preparation .…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, it has been reported that an individual consuming an American diet can ingest between 39,000 and 52,000 pieces of microplastics from food and beverages each year. 10 Infants and toddlers are more susceptible to potential health impacts of micro-and nanoplastics than adults, 11 making their exposure to these particles and associated health risks a significant concern. A recent study focused on the release of microplastics from polypropylene-based baby feeding bottles during formula preparation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nearly half of this plastic was used for disposable packaging, leading to immense generation of plastic waste. By 2050, global plastic waste is estimated to reach 12 billion tons [ 2 ]. The limited recycling and reuse of plastics result in the continuous accumulation of plastic waste in the environment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%